COVID-19: global pandemic with divergent waves: an exigent public health concern worldwide with special context to Indian scenario - Sharaf, Shehna; Athikkavil, Faisal Moossa; Varghese, Shiny Deena; Sreekumar, Sreelekshmi; Ramakrishnan, Reshmi; Varghese, Jeslin; Pillai, Lakshmi Sree Dharan; Regidi, Saikant; Aprem, Abi Santhosh (International Journal Of Community Medicine And Public Health, 2022)
The review discusses, how the COVID-19 virus evolved to the present form, genome organization and genetic variation of SARS- CoV-2 prevalent globally with special emphasis on Indian strains, a comparison of the first vs. second wave in terms of infectivity and transmission patterns. The population impacted, importance of surveillance, study of genetic variants of COVID-19 virus, development of diagnostics developed in First and second waves of infection and preventive measures like physical means, vaccine administration and treatment strategies using different classes of anti-viral, anti-inflammatory, antibiotic and corticosteroid drugs. The study used the detailed and qualitative online research. The literature studies were conducted to explore the havoc of the COVID-19 Pandemic from the very beginning era to current and future repercussions in worldwide with special context to India. The idea of our work is to be on a high alert and vigilant in the constant studying of the varying characteristics of the pandemic and to produce resources and be able to modify treatment methodologies quickly, if needed, and disseminate our work to the scientific world and community as soon as possible for coordinating a global action to cut off the inevitable future waves of this pandemic. Securing vaccine is the most concern, along with the strategies that could be forward to strengthen the health care system. This paper gives insight by warning the third wave, unless taken utmost care by each individual, national as well international organization could be catastrophic to the entire World.